2017
DOI: 10.1155/2017/1725354
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibulin-3 as a Potential Biomarker for Patients with Asbestos-Related Diseases in the Han Population

Abstract: Fibulin-3 has been reported as a potential biomarker for mesothelioma. However, little is known about the diagnostic efficacies of fibulin-3 for asbestos-related diseases (ARDs) in China. This study was to investigate the utility of fibulin-3 for asbestos exposure and ARDs. A total of 430 subjects were recruited from Southeast China, including healthy individuals, asbestos-exposed (AE) individuals, and patients with pleural plaques (PP), asbestosis, and malignant pleural mesothelioma (MPM). Plasma fibulin-3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Many oncogenes, anti-oncogenes and pathways participate in the tumorigenesis process and metastasis. FBLN3, which is also called epidermal growth factor-containing fibulin-like extracellular matrix protein 1 (EFEMP1), is related to many diseases, such as age-related macular degeneration [7], knee osteoarthritis [8], asbestos-related diseases [9], rheumatoid arthritis [10], mesothelioma [11], glioblastoma [12], osteosarcoma [13], ovarian cancer [14] and cervical cancer [15]. Many studies have reported that the fibulin family, which consists of 7 secreted extracellular glycoproteins, is involved in cell morphology maintenance, cell growth, adhesion and movement.…”
Section: Discussionmentioning
confidence: 99%
“…Many oncogenes, anti-oncogenes and pathways participate in the tumorigenesis process and metastasis. FBLN3, which is also called epidermal growth factor-containing fibulin-like extracellular matrix protein 1 (EFEMP1), is related to many diseases, such as age-related macular degeneration [7], knee osteoarthritis [8], asbestos-related diseases [9], rheumatoid arthritis [10], mesothelioma [11], glioblastoma [12], osteosarcoma [13], ovarian cancer [14] and cervical cancer [15]. Many studies have reported that the fibulin family, which consists of 7 secreted extracellular glycoproteins, is involved in cell morphology maintenance, cell growth, adhesion and movement.…”
Section: Discussionmentioning
confidence: 99%
“…Human fibulin-3, also known as epidermal growth factor containing fibulin-like extracellular matrix protein 1 (EFEMP1), has also been investigated as a potential biomarker for asbestos-related diseases, especially for MM [31][32][33]. It is a member of a family of extracellular matrix glycoproteins [34] that have been proposed to be important in the regulation of cell proliferation and migration and to act as tumour suppressors or activators in different cancers [34][35][36][37][38].…”
Section: Fibulinmentioning
confidence: 99%
“…The results also showed that subjects in the asbestosis group had a higher median fibulin-3 level compared to those in the control group. Their study proposed that fibulin-3 could be a potential biomarker for early screening of MM, but not for other asbestosrelated diseases [33].…”
Section: Fibulinmentioning
confidence: 99%
“…The MPM patients with epithelioid subtype had higher levels of mesothelin than those with sarcomatoid subtype ( 189 ). Another highly promising biomarker is the circulating glycoprotein fibulin-3 ( 190 ). A study population conducted by Pass et al showed elevated fibulin-3 levels both in plasma (specificity of 94% and sensitivity of 100%) and pleural effusion (specificity of 93% and sensitivity of 84%) of MPM patients, distinguishing healthy persons with exposure to asbestos from patients with MPM ( 180 ).…”
Section: New Therapeutic Approaches and Novel Molecular Targetsmentioning
confidence: 99%